Stagnation Zones for 𝒜-Harmonic Functions on Canonical Domains. (4th February 2010) - Miklyukov, Vladimir M.; Rasila, Antti; Vuorinen, Matti
Abstract : We study stagnation zones of𝒜 -harmonic functions on canonical domains in the Euclideann -dimensional space. Phragmén-Lindelöf type theorems are proved.